A selective fluorescent probe for the detection of Cd2+ in different buffer solutions and water. Issue 30 (11th July 2016) - Xu, Zheng; Li, Guoqiang; Ren, Yuan-Yuan; Huang, Hua; Wen, Xiaoping; Xu, Qiang; Fan, Xiaotian; Huang, Zhao; Huang, Junhai; Xu, Lin
Abstract : A fluorescent probeNHQ, which exhibited excellent selectivity toward Cd 2+ in different buffer solutions such as Tris-HCl buffer solution, HEPES buffer solution, and PBS buffer solution, and even in water, was developed. Abstract : A simple fluorescent probeNHQ based on quinoline was successfully prepared via one-step synthesis. The probeNHQ exhibited "turn-on" fluorescence and excellent selectivity toward Cd 2+ in different buffer solutions such as Tris-HCl buffer solution, HEPES buffer solution, and PBS buffer solution, and even in water. Moreover, the binding model ofNHQ with Cd 2+ was definitely confirmed by the single crystal X-ray diffraction studies of the complex.